New insights into the role of tetraspanin 6, 7, and 8 in physiology and pathology - Monika Mrozowska; Tomasz Górnicki; Mateusz Olbromski; Aleksandra Izabela Partyńska; Piotr Dzięgiel; Agnieszka Rusak (Cancer Medicine)
Abstract Background The tetraspanin (TSPAN) family comprises 33 membrane receptors involved in various physiological processes in humans. Tetrasapanins are surface proteins expressed in cells of various organisms. They are localised to the cell membrane by four transmembrane domains (TM4SF). These domains bind several cell surface receptors and signalling proteins to tetraspanin‐enriched lipid microdomains (TERM or TEM). Tetraspanins play a critical role in anchoring many proteins. They also act as a scaffold for cell signalling proteins. Aim To summarise how tetraspanins 6, 7 and 8 contribute to the carcinogenesis process in different types of cancer. Methods To provide a comprehensive review of the role of tetraspanins 6, 7 and 8 in cancer biology, we conducted a thorough search in PubMed, Embase and performed manual search of reference list to collect and extract data. Discussion The assembly of tetraspanins covers an area of approximately 100–400 nm. Tetraspanins are involved in various biological processes such as membrane fusion, aggregation, proliferation, adhesion, cell migration and differentiation. They can also regulate integrins, cell surface receptors and signalling molecules. Tetraspanins form direct bonds with proteins and other members of the tetraspanin family, forming a hierarchical network of interactions and are thought to be involved in cell and membrane compartmentalisation. Tetraspanins have been implicated in cancer progression and have been shown to have multiple binding partners and to promote cancer progression and metastasis. Clinical studies have documented a correlation between the level of tetraspanin expression and the prediction of cancer progression, including breast and lung cancer. Conclusions Tetraspanins are understudied in almost all cell types and their functions are not clearly defined. Fortunately, it has been possible to identify the basic mechanisms underlying the biological role of these proteins. Therefore, the purpose of this review is to describe the roles of tetraspanins 6, 7 and 8.